A peridynamic model for fracture analysis of polycrystalline BCC-Fe associated with molecular dynamics simulation. (August 2021) - Zhu, Jiaqi; He, Xiaoqiao; Yang, Dong; Bie, Zhiwu; Mei, Huanhuan; Tian, Xiaobao
Highlights: A PD model is proposed to investigate cohesive fracture of polycrystal Fe. Effective traction-separation relation of BCC-Fe is obtained from MD simulation. Atomic-scale information is transferred to micro-scale via energy equivalence. A good agreement between the proposed PD model and classical CZM is found. Dynamic fracture characteristics are examined using the proposed PD model. Abstract: In this work, based on the traction-separation (T-S) constitutive relations extracted from molecular dynamics (MD) simulation, a peridynamics (PD) model is proposed to investigate the crack propagation behavior of the polycrystal BBC-Fe under mode I loading condition. MD simulation is carried out to give an insight into the cracking process and fracture mechanism according to the analysis of atomic configuration and stress distribution. The atomic stress at the crack tip with respect to the opening distance is tracked during the steady cracking stage to provide a stable T-S relation. The fracture parameters of single crystal Fe are obtained via MD simulation, based on which the PD parameters are obtained through an energy equivalent method. After that, a PD approach combined with cohesive zone model (CZM) is proposed to study the mode I fracture in polycrystal Fe. A good agreement has been found between the proposed PD model and the classical CZM based on a quasi-static splitting test of a single Fe crystal. Subsequently, PD simulations are performed concerning the dynamic crack propagation in a polycrystal Fe. What's more, the effect of grain size, the grain boundary strength and the horizon size of PD on the fracture characteristics are examined. It can be concluded that the T-S relation originated from classical cohesive theory can be regarded as an effective bridge between MD and PD. This work provides a new thought to study the fracture behavior of polycrystals from the atomic deformation mechanism to micro-fracture description.